2015
DOI: 10.1186/s12913-015-0976-z
|View full text |Cite
|
Sign up to set email alerts
|

Process of care in outpatient Integrative healthcare facilities: a systematic review of clinical trials

Abstract: BackgroundPatients currently integrate complementary medicine (CM) and allopathic, choosing a combination of therapies rather than a single therapy in isolation. Understanding integrative healthcare (IHC) extends beyond evaluation of specific therapies to encompass evaluations of multidisciplinary complex interventions. IHC is defined as a therapeutic strategy integrating conventional and complementary medical practices and practitioners in a shared care setting to administer an individualized treatment plan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 79 publications
(174 reference statements)
0
6
0
1
Order By: Relevance
“…We used four key publications selected by project staff to represent different aspects of care coordination research (clinical integration, implementation of technological advances, social network analysis of provider relationships and interpersonal relationships between providers) as seed articles for a forward search 1 2 6 7. We screened studies included in 127 systematic reviews on care coordination to obtain a broad range of care coordination approaches 3–5 8–131. The reviews addressed common chronic conditions managed in primary as well as specialty care, cancer care, palliative care, comorbidity and complexity, personnel specialising in care coordination, frameworks and strategies to promote coordination, technology supporting coordination, settings for temporary care such as emergency departments and care models applied to specific populations.…”
Section: Methodsmentioning
confidence: 99%
“…We used four key publications selected by project staff to represent different aspects of care coordination research (clinical integration, implementation of technological advances, social network analysis of provider relationships and interpersonal relationships between providers) as seed articles for a forward search 1 2 6 7. We screened studies included in 127 systematic reviews on care coordination to obtain a broad range of care coordination approaches 3–5 8–131. The reviews addressed common chronic conditions managed in primary as well as specialty care, cancer care, palliative care, comorbidity and complexity, personnel specialising in care coordination, frameworks and strategies to promote coordination, technology supporting coordination, settings for temporary care such as emergency departments and care models applied to specific populations.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, due to the increased data demonstrating the effectiveness of complementary practices to help treat chronic illness, and increased conventional practitioners practicing complementary health approaches, the integrative medicine model emerged to combine conventional and complementary methods to deliver holistic, patient-centered care. [15][16][17][18] Integrative models have already shown benefits of mindfulness-based therapies utilized by their patients. For example, a prospective cohort study of Kaiser Permanente Colorado patients with chronic pain, chronic illness, or a stress-related problem and without uncontrolled psychiatric illnesses found that an eight-week MBSR program led to significant improvements in selfreported pain, psychological symptoms, and reduced health services utilization.…”
Section: Introductionmentioning
confidence: 99%
“…While previous reviews of the effectiveness of IHC have been published, the literature searches are now more than seven years old; as such, these reviews no longer reflect the state of the art. Furthermore, the scope of previous reviews of IHC have been limited to clinical outcomes and processes of care; no known reviews have explored the impact of IHC on service‐related outcomes. A contemporary, comprehensive and systematic review of the best available evidence of the effectiveness of integrative healthcare for the management of chronic disease, which considers both patient‐ and service‐related outcomes, is therefore warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the scope of previous reviews of IHC have been limited to clinical outcomes 29 and processes of care 30 ; no known reviews have explored the impact of IHC on service-related outcomes.…”
mentioning
confidence: 99%